EFEKTIVITAS MODEL EDUKASI DAN DUKUNGAN MENYUSUI UNTUK MENINGKATKAN BREASTFEEDING SELF-EFFICACY DAN PEMBERIAN ASI EKSKLUSIF: SCOPING REVIEW - Sembiring, Gaipyana; Damayani, Ayi Diah; Aziz, Muhammad Alamsyah; Gurnida, Dida Akhmad (Poltekkes Kemenkes Bandung, 2024)
WHO and UNICEF data state that the level of exclusive breastfeeding in the world is below the target of 40%. Breastfeeding self-efficacy was identified as one of the strongest modifiable predictors. This scoping review aimed to analyze the effectiveness of breastfeeding education models to increase breastfeeding self-efficacy and exclusive breastfeeding. The design of this article is a systematic review using the Preferred Reporting Items for Literature Review and Meta-Analyses (PRISMA) method. Article searches used electronic databases from Scopus, Science Direct, PubMed and Sage. The keywords in the article search are